The effect of human leukocyte antigen disparity on cyclosporine neurotoxicity after allogeneic bone marrow transplantation. - Zimmer, W E; Hourihane, J M; Wang, H Z; Schriber, J R (American Journal of Neuroradiology, 1998)
PURPOSE We examined the relationship between human leukocyte antigen (HLA) matching and the development of cyclosporine (CyA) neurotoxicity in patients undergoing allogeneic bone marrow transplantation, and determined the frequency and imaging characteristics of CyA neurotoxicity in these patients.METHODS Records of 87 patients who underwent allogeneic bone marrow transplantation were reviewed. Eight patients who presented with visual disturbance and/or seizures and had MR imaging within 24 hours were identified. Transplant donor relatedness was examined, and patients' imaging studies were reviewed. Clinical parameters, including blood pressure, CyA, creatinine, and magnesium levels, and the presence of graft-versus-host disease were reviewed.RESULTS CyA neurotoxicity was seen more frequently in HLA-mismatched and unrelated donor transplants. The frequency of CyA neurotoxicity was 4% for patients with a 5/6 or 6/6 HLA match, 13% for matched unrelated donor transplants, and 50% for haplotypic 3/6 or 4/6 transplants. Patients with matched unrelated donor transplants and haplotypic transplants presented earlier in the posttransplant time course and had decreased survival time relative to patients with HLA-matched transplants. Imaging abnormalities most commonly affected the occipital lobes and the posterior cerebral hemispheres; both cortical and white matter involvement was identifiable as T1 hypointense and T2 hyperintense signal with associated gyral swelling and sulcal effacement on the initial MR studies. Hypodensity in the affected areas was noted on CT scans. Contrast enhancement was seen in HLA-mismatched and unrelated transplants only. Follow-up imaging showed interval decreases in subcortical edema; however, residual signal abnormality, primarily affecting the cortex, was present in all cases and seen best on proton density-weighted MR images.CONCLUSION The frequency of severe CyA neurotoxicity increases with increasing HLA disparity, suggesting that immune factors may play a role. CyA neurotoxicity appears to represent a spectrum of disease processes. Disruption of the blood-brain barrier as well as hypoxic or vasculitic cortical injury resulting in MR-detectable cortical signal abnormalities may occur in severe cases.